A Study on Influence of Mother Tongue in Learning English Language Among High School Students - Mageshwari, D. Uma; Selvakumar, Y. Stanly (Journal of Advanced Research in English & Education, 2023)
The essay examines the difficulties high school students have speaking English as a result of the influence of their native tongue. There are efforts underway in Chennai to require high school students and students in the classroom to speak in English. Mother tongues may have a negative impact on the expansion of the English language in this area. Both English as a second language (L2) and mother tongue (L1) have unique characteristics in terms of structure, syntax, lexicon, phonology, morphology, and other areas. The students are perplexed by the differences between their mother tongue and English. Numerous researchers have already conducted extensive research on the subject of mother tongue influence on learning English as a second language. This study report also examines potential remedies and fixes for the problems mentioned above. The findings demonstrate how mother tongue influence affects high school students’ spoken and written English. It also demonstrates how crucial mother tongue is to students’ academic success. Last but not least, students’ mother tongues prevent them from learning the grammar of other languages. However, this study discovered that high school students’ mother tongues mattered.